‘But’ Implicatures: A Study of the Effect of Working Memory and Argument Characteristics - Janssens, Leen; Schaeken, Walter (Frontiers in Psychology, 2016)
This study aimed to investigate the possible cognitive costs involved in processing the implicatures from but and the conclusion introducing words so and nevertheless. Adult participants were asked to indicate the conclusion that the person in the story would make, based on ‘p but q’ sentences constructed as indirect distancing contrasts. Additionally, while performing this task, participants’ working memory was burdened with a secondary dot recall task in four conditions ranging from no working memory load to high load. The results showed that working memory load did not influence participants’ performance on the implicature task. This finding might be interpreted to suggest that working memory is not involved in inferring the implicatures from but, so and nevertheless. We also found that the content of the arguments played a very important role. Whenever a strong argument is combined with a weak argument, participants mostly base their conclusion on the strong argument and consequently ignore the conventional interpretation of but (and so and nevertheless). Additionally, we found an effect of axiological value, which is in line with the positive-negative asymmetry theory.